Sexual Violence in the Educational Sector from a Criminological Perspective - Arqon, Mohammad; Chandra, Febrian; Elfisa, Yesi; Kusaimah, Kusaimah; Fathullah Saputra, Dipo; Amirullah, M. Aria; Tauhid, Tauhid (Jurnal Penelitian Inovatif, 2025)
This research is motivated by the increasing cases of sexual violence in educational institutions, which have severe consequences for victims, both physically, psychologically, and socially. This phenomenon is often ignored or covered up by educational institutions and society, making it difficult for victims to obtain justice. From a criminological perspective, sexual violence is influenced by power imbalances, weak legal systems, and social norms that are still permissive towards harassment. The purpose of this study is to analyze the traumatic impacts experienced by victims of sexual violence in educational settings and explore effective prevention strategies. Additionally, this study aims to identify the primary causes of sexual violence and provide policy recommendations for educational institutions and relevant stakeholders. The method used in this research is normative legal research with a qualitative approach. Data collection techniques include literature review, analysis of relevant laws and regulations, and previous studies on sexual violence in the education sector. The results and discussion indicate that victims experience trauma in various aspects of their lives, including anxiety, depression, decreased academic performance, and social marginalization. The lack of effective protection mechanisms in educational institutions increases the risk of revictimization. The conclusion of this study emphasizes the need for a comprehensive approach to preventing sexual violence through strict legal policies, gender-awareness education, and strengthened psychosocial support for victims. Collaboration between the government, educational institutions, and society is key to creating a safe and violence-free educational environment.